The effect of composted and non-composted poultry litter on survival and reproduction of Folsomia candida - Ana Paula Maccari; Julia Corá Segat; Manuela Testa; Carolina Riviera Duarte Maluche-Baretta; Dilmar Baretta (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The objective was to evaluate the effect of the application of composted and non-composted poultry litter, as fertilizer in agricultural areas, on the survival and reproduction of the springtails (Folsomia candida) through standardized ecotoxicological tests. Methods The treatments included in the application of composted and non-composted poultry litter on Entisol were in the following doses 0, 10, 20, 40, 60, 80, 100 t ha-1, for the lethality test, and 0, 5, 7.5, 10, 15, 30, 40, 60 t ha-1 for the reproduction test. Results For the composted litter, the LC50 value was 76.45 t ha-1 and for EC50, it was 17.96 t ha-1. For the non-composted poultry litter, the values of LC50 was 43.12t ha-1 and EC50 value was 19.36 t ha-1. Conclusion The highest toxicity was observed in the non-composted litter, emphasizing the importance of stabilization of the organic compound before its use as fertilizer.